Clinical Utility of Enzymes, Electrolyte and Uric Acid in Different Stages of Chronic Pancreatitis - Tarun Kumar Naik, Manish Kumar Khare,; Ambad, Ranjit S. (International Journal of Innovative Research in Medical Science, 2017)
Purpose: - The present study examines the clinical utility of enzymes, electrolytes and uric acid in different stages of chronic pancreatitis admitted at Chandulal Chandrakar Memorial Medical College and Hospital Kachandur, Durg. Methods: - A total number of 35 male subjects were selected at CCM Medical College Hospital Durg. 35 subjects are suffering from chronic pancreatitis average age range of 40 to 70 years. 35 subjects age, sex matched was selected for control group. Controls were clinically and physically normal and healthy. The study was conducted in the period of May 2015 to Feb 2017. Results and Conclusion: - There were 35 patients suffering from chronic pancreatitis selected for study group and 35 normal healthy for control group. Levels of serum amylase, serum lipase, serum electrolytes and serum uric acid are given in following table no2. Most pancreatic function tests have high sensitivity and specificity to accurately diagnose patients with advanced CP. Serum lipase levels due to pancreatic disorders closely parallel the changes of serum amylase except that serum lipase may remain elevated longer than amylase (up to 2 weeks). Elevated serum amylase and lipase are strong evidence for a pancreatic process. When the serum amylase is elevated and the lipase is normal, non-pancreatic causes of the hyperamylasemia are more likely.